The Theory of the Rule 'Ijtihad Cannot Be Overturned by another Ijtihad' and Its Application in the Case of Bid'ah Divorce - Riandi, Muhamad (Sharia Journal and Education Center Publishing, 2024)
Abstract This study delves into the theoretical principle of